Do chronic pain and comorbidities affect brain function in sickle cell patients? A systematic review of neuroimaging and treatment approaches. Issue 9 (September 2019) - Da Silva, Joyce T.; Letzen, Janelle E.; Haythornthwaite, Jennifer A.; Finan, Patrick H.; Campbell, Claudia M.; Seminowicz, David A.
Abstract : Abstract: Sickle cell disease (SCD) is a medical condition in which chronic pain is common and negatively impacts psychosocial function and quality of life. Although the brain mechanisms underlying chronic pain are well studied in other painful conditions, the brain mechanisms underlying chronic pain and the associated psychosocial comorbidities are not well established in SCD. A growing literature demonstrates the effect of treatment of chronic pain, including pharmacological and nonpharmacological treatments, on brain function. The present systematic review aimed to (1) determine the effects of chronic pain and psychosocial comorbidities on brain function of patients with SCD; (2) summarize pharmacological and nonpharmacological approaches to treat these symptoms; and (3) identify areas for further investigation of potential beneficial effects of treatments on brain function. Titles were screened using predefined criteria, including SCD, and abstracts and full texts were reviewed by 2 independent reviewers. A total of 1167 SCD articles were identified, and 86 full articles were included covering 3 sections: chronic pain (4 studies), psychosocial comorbidities (11 studies), and pharmacological and nonpharmacological treatments (71 studies). Neuroimaging evidence demonstrates aberrant neural processing related to chronic pain and psychosocial comorbidities in SCD beyond ischemic stroke and cerebral hemorrhage. Although neuroimaging studies show an important role for psychological factors, pain management is nearly exclusively based on opioids. Behavior therapy seems useful to improve psychological symptoms as well as chronic pain and quality of life. Further investigation is required with larger cohorts, matched controls, and examination of treatment-related neural mechanisms. Abstract : Supplemental Digital Content is Available in the Text.